Artificial modelling of unsaturated tests considering the suction control on porous collapsible clay. (November 2019) - Ruge, J C
Abstract: Soils with a tendency to show phenomena of collapsibility generally have a susceptibility to be controlled by partial saturation, due to its structural configuration which reveal in some cases bonds of cementing minerals, that can be broken in process of wetting. This cementation is governed by the lateritic genesis, as well as for a microporal predominance. Laboratory tests that intend to reproduce the unsaturated condition, need a suction control to simulate properly the levels of stress required in the sample, according with the in-situ stresses presents in the soil mass. However, these tests are difficult to have access to given that they have a complicated assembly and can last several days (even months), due to the benefit in the resistance imposed by the suction on the soil. For this reason, it is extremely important to validate numerically by means of an appropriate constitutive law, at least at the laboratory level, the unsaturated response of a material. In this case a collapsible porous clay of lateritic origin, cause the high dependency of specialized laboratory tests can lead to non-necessaries delayed researches, that can impact in the economy of any project. In this research, an emphasis is placed on the numerical simulation of partially saturated tests through a hypoplastic constitutive model that involves suction in its mathematical formulation. The results are oriented to show the dependence of the suction with the shear strength of the material.